The Implementation For The Seeker Confidence After The Enactment Of The Constitutional Court Decision No. 97/Puu-Xiv / 2016 Concerning Population Administration In Rembang District - Denni Saputra; Akhmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
Problems of this research is how the implementation for the seeker of confidence after the enactment of the Constitutional Court decision No. 97 / PUU-XIV / 2016 concerning Population Administration; how the implementation of the marriage for the seeker of trust; how the solution implementation barriers for seeker confidence of marital trust; how the notary authority in making authentic act for marriage seeker of confidence. The method used in this research is empirical juridical approach derived from data obtained from the collection of primary data and secondary data, and then analysed by qualitative descriptive analysis method. The data collection technique used was the study of literature (laws, and books about this research) and field studies (interviews with respondents who made sources). Data analysis technique using qualitative data analysis.Based on the findings of researchers showed that appear false assumption of the seeker of the belief that the implementation of the marriage for the seeker of trust cannot be empowered by law, cannot be served their implementation by the competent authority; The absence of laws that specifically regulate: the Marriage of the seeker, recognition that the seeker of trust including one of the official religion; providing solutions to create and revise laws pertaining to the seeker of such beliefs in terms of recognition as a religion and the administration of residence; Notary involves authority until now could not be done on the implementation of the marriage for the seeker of Faith, a notary has no authority in making authentic act, in the absence of legislation governing it. But it can be circumvented by issuing a certificate in Partij deed.Keywords: Marriage; Seeker Confidence; Population Administration.